Modeling observations of solar coronal mass ejections with heliospheric imagers verified with the Heliophysics System Observatory. Issue 7 (29th July 2017) - Möstl, C.; Isavnin, A.; Boakes, P. D.; Kilpua, E. K. J.; Davies, J. A.; Harrison, R. A.; Barnes, D.; Krupar, V.; Eastwood, J. P.; Good, S. W.; Forsyth, R. J.; Bothmer, V.; et al.
Abstract: We present an advance toward accurately predicting the arrivals of coronal mass ejections (CMEs) at the terrestrial planets, including Earth. For the first time, we are able to assess a CME prediction model using data over two thirds of a solar cycle of observations with the Heliophysics System Observatory. We validate modeling results of 1337 CMEs observed with the Solar Terrestrial Relations Observatory (STEREO) heliospheric imagers (HI) (science data) from 8 years of observations by five in situ observing spacecraft. We use the self‐similar expansion model for CME fronts assuming 60° longitudinal width, constant speed, and constant propagation direction. With these assumptions we find that 23%–35% of all CMEs that were predicted to hit a certain spacecraft lead to clear in situ signatures, so that for one correct prediction, two to three false alarms would have been issued. In addition, we find that the prediction accuracy does not degrade with the HI longitudinal separation from Earth. Predicted arrival times are on average within 2.6 ± 16.6 h difference of the in situ arrival time, similar to analytical and numerical modeling, and a true skill statistic of 0.21. We also discuss various factors that may improve the accuracy of space weather forecasting using wide‐angle heliospheric imager observations. These results form a first‐order approximated baseline of the prediction accuracy that is possible with HI and other methods used for data by an operational space weather mission at the Sun‐Earth L5 point. Plain Language Summary: Solar storms are formed by incredibly powerful explosions on the Sun and travel as clouds of plasma threaded by magnetic fields through the solar system. Depending on their propagation direction, they may impact planets such as Earth, where they elicit colorful aurorae or, in very seldom cases, can lead to power failures with potentially tremendous economical and societal effects, thus posing a serious natural hazard. In this work, we have shown how well the solar storm impact can be forecasted when using a special type of instrument that can actually image the solar storms as they propagate toward the planets and even as they sweep over them. Our analysis includes two thirds of a solar cycle with 8 years of data, and spacecraft at Mercury, Venus, Earth, and in the solar wind to check on the correctness of our predictions. We could forecast the arrival time within ±16 h, and for one correct impact there are two to three false alarms. This forms a new baseline for the science of space weather prediction. Clearly, the modeling should be further improved to be used on a daily basis for a space weather mission to the Sun‐Earth L5 point. Key Points: Hindsight predictions of CMEs by modeling observations from the STEREO heliospheric imagers science data are analyzed for 2007‐2014 About one out of four predicted CME arrivals is observed in situ as a magnetic obstacle by MESSENGER, Venus Express, Wind, and STEREO A/B Although using strong assumptions on CME physics, prediction accuracies for CME arrival times are similar to numerical or analytical models